2015
DOI: 10.1039/c5cp01177a
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmons in quantum-sized noble-metal clusters: TDDFT quantum calculations and the classical picture of charge oscillations

Abstract: The localized surface-plasmon resonance of metal nanoparticles corresponds to a classical charge oscillation of the quasi-free conduction electrons. In the case of noble-metal nanoparticles, interband transitions from the d electrons influence the spectra strongly. In addition, the inhomogeneity of the nanoparticles at the atomistic level becomes important for small sizes. Using the time-evolution formulation of time-dependent density-functional theory, we show that in spherical 147-atom silver clusters, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 47 publications
(162 reference statements)
0
40
0
Order By: Relevance
“…From this point of view, the Sternheimer approach and wave-packet propagation approach have an advantage versus iterative TDDFT: former approaches only need the xc potential, and do not involve the TDDFT kernel. Fortunately, local and semi-local functionals correctly capture trends of the plasmonic response in nano-particles as was well documented in the past [73], and are still widely used [82].…”
Section: Choice Of the Exchange-correlation Functionalmentioning
confidence: 93%
“…From this point of view, the Sternheimer approach and wave-packet propagation approach have an advantage versus iterative TDDFT: former approaches only need the xc potential, and do not involve the TDDFT kernel. Fortunately, local and semi-local functionals correctly capture trends of the plasmonic response in nano-particles as was well documented in the past [73], and are still widely used [82].…”
Section: Choice Of the Exchange-correlation Functionalmentioning
confidence: 93%
“…Time-dependent density-functional theory (TDDFT) 1 built on top of Kohn-Sham (KS) density-functional theory (DFT) 2,3 is a powerful tool in computational physics and chemistry for accessing the optical properties of matter. 4,5 Starting from seminal works on jellium nanoparticles, [6][7][8] TDDFT has become a standard tool for modeling plasmonic response from a quantummechanical perspective, 9,10 and proven to be useful for calculating the response of individual nanoparticles, [11][12][13][14][15][16][17][18][19][20][21] and their compounds [22][23][24][25][26][27][28][29][30][31][32] as well as other plasmonic materials. [33][34][35][36] Additionally, a number of models and concepts have been developed for quantifying and understanding plasmonic character within the TDDFT framework.…”
Section: Introductionmentioning
confidence: 99%
“…36 Recently, a few TDDFT studies have been performed on Ag n clusters with n ∼ 8 − 300 atoms. 22,24,[37][38][39][40][41][42][43][44][45] However, while most studies used a local or semi-local formulation for the exchange and correlation functional, one of us have shown that the use of a hybrid functional is required 3 to correctly describe the excitations of d-type electrons which present charge-transfer and Rydberg characters. 46,47 Such excitations cannot be described within TDDFT with a local or semi-local density functional in the adiabatic approximation used in standard calculations.…”
Section: Introductionmentioning
confidence: 99%